Registration of Deeds of Encumbrance That Exceed the Time Limit in Badung Regency - Kadek Ayu Rima Ratnasari; I Made Suwitra; Nengah Renaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the registration of Deeds of Mortgage (APHT) that exceed the 7 (seven) day time limit in Badung Regency and the legal consequences that arise from this. The research uses empirical legal methods with a legislative, analytical, case, and legal sociology approach. Data was obtained through interviews with PPAT and the Badung Regency Land Office (BPN) as well as a study of secondary legal materials. The results of the study show that delays in APHT registration still occur both through the manual (offline) and electronic (HT-el) systems. The contributing factors include negligence or workload of PPAT, incomplete documents from the parties, administrative obstacles at the Land Office, and technical disruptions to the electronic system. Legally, delays do not invalidate APHT, but they delay the creation of mortgage rights because these rights only have legal force from the date of recording in the Land Registry. As a result, creditors do not obtain preferential rights and full legal protection before registration is carried out. PPATs who are late may be subject to administrative sanctions in accordance with official regulations. Based on the theories of utility, legal protection, and legal certainty, delays in APHT registration reduce the effectiveness of creditor protection and create potential legal uncertainty. Therefore, it is necessary to improve supervision and guidance for PPATs, as well as optimize the HT-el system to ensure legal certainty and protection in the practice of registering Mortgage Rights.